Virtual Reality as Experiential Learning A Case Study in Anxiety and Walking the Plank. - Collette, D.
While the pedagogical benefits of experiential learning are well known, classroom technology is a more contentious topic. In my experience, philosophy instructors are hesitant to embrace technology in their pedagogy. A great deal of this trepidation is justified: when technology serves only to replicate existing methods without contributing to course objectives, it unnecessarily adds extra work for the instructor and can even be a distraction from learning. However, I believe, if applied appropriately, technology can be used to positively enhance the philosophy classroom experience in ways that are not possible in traditional classroom settings ? including new ways of experiential learning. To demonstrate this, I offer a case study of implementing virtual reality (VR) as a tool for experiential learning of philosophy. I show how having students ?walk a plank? off a skyscraper in VR allowed me to exceed my course objectives for my Existentialism course in particularly effective ways that I could not have done without this technology.
Keywords: Philosophy -- Periodicals; Teaching -- Periodicals